Towards empowerment of women through micro financing: experience of Rashtriya Mahila Kosh (Note) - Misra, Indira (1997)
With focus on potentials of micro financing in powerty amelioration and empowerment of women, the author analyses the concept, its features and significance. Giving a bird's-eye view of micro finance credit programmes in several countries to impart a comparative perspective, she provides relevant analytical information on Rashtriya Mahila Kosh (RMK), its origin, objectives, source of funding, structure, pattern of credit, and role of NGOs and self-help groups in promoting RMK activities. She also touches upon RMK's future prospects. - Reproduced
Keywords: Note; Womens employment - India; Womens employment